1990
DOI: 10.1097/00007890-199009000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor and Hyperacute Rejection

Abstract: The pathogenesis of hyperacute transplantation reactions includes the activation of a cascade of nonspecific inflammatory reactions that precipitates the destruction of the target organ. Platelet-activating factor (PAF) represents an important component of these inflammatory cascades, and we have examined the influence of a specific PAF receptor antagonist (SRI 63-441) on the inhibition of hyperacute rejection in two experimental models, the rejection of rat cardiac allografts by presensitized recipients and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although in this last work glomerular filtration rate was not measured, the reduction of thromboxane A 2 was associated with a haemodynamic and pathologic benefit. Also, other authors [ 15–18] found that PAF receptor antagonists were able to abolish the full histologic picture of HXR. However, whether these pharmacological agents interfere with the action of complement is controversial [ 22].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although in this last work glomerular filtration rate was not measured, the reduction of thromboxane A 2 was associated with a haemodynamic and pathologic benefit. Also, other authors [ 15–18] found that PAF receptor antagonists were able to abolish the full histologic picture of HXR. However, whether these pharmacological agents interfere with the action of complement is controversial [ 22].…”
Section: Discussionmentioning
confidence: 94%
“…It has been clearly demonstrated that PAF contributes to the pathogenesis of hyperacute allograft rejection in presensitized hosts [ 14]. On the other hand, single administration of PAF receptor antagonists has shown a protective effect in xenograft concordant and discordant models [ 15–19]. However, in some instances PAF antagonists have not provided histologic benefit to HXR [ 20], or they needed to be combined with other agents to prolong xenograft survival [ 21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vascular damage, activation of platelets and coagulation with thrombosis within the xenograft vasculature could be exacerbated by the associated loss of vascular ATPDase/CD39, a putative thromboregulatory factor. 69,70 Inhibition of platelet aggregation by treatment of xenograft recipients with antagonists to the platelet fibrinogen receptor, GPIIbIIIa, 80,127 by the use of P-selectin or PAF antagonists, 84,128,129 or by administration of a soluble ATPDase 130 has been generally shown to prolong graft survival in several discordant xenotransplantation models.…”
Section: Platelet Activation and Thromboregulationmentioning
confidence: 99%